2021
DOI: 10.1038/s41598-021-93573-2
|View full text |Cite
|
Sign up to set email alerts
|

CPT to RVU conversion improves model performance in the prediction of surgical case length

Abstract: Methods used to predict surgical case time often rely upon the current procedural terminology (CPT) code as a nominal variable to train machine-learned models, however this limits the ability of the model to incorporate new procedures and adds complexity as the number of unique procedures increases. The relative value unit (RVU, a consensus-derived billing indicator) can serve as a proxy for procedure workload and could replace the CPT code as a primary feature for models that predict surgical case length. Usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…However, total wRVU has been demonstrated to correlate well with case complexity in multiple surgical specialties. 16,25,26 Additionally, the mFI-5 has been validated as a tool in predicting complications after free flap reconstruction. 27 We uniquely utilized a combination of these factors in an attempt to control for operative complexity and patient preoperative health.…”
Section: Discussionmentioning
confidence: 99%
“…However, total wRVU has been demonstrated to correlate well with case complexity in multiple surgical specialties. 16,25,26 Additionally, the mFI-5 has been validated as a tool in predicting complications after free flap reconstruction. 27 We uniquely utilized a combination of these factors in an attempt to control for operative complexity and patient preoperative health.…”
Section: Discussionmentioning
confidence: 99%
“…This may, however, reflect the design of the experiment and the limited set of models assessed. For example, we would expect sign-out time and CPT code usage to partially reflect case complexity and uncertainty 40 , where more challenging cases could impact the measurement of relative value units (RVUs). However, sign-out time data is only a one-sided representation of the complexity of the text and may not represent true complexity in several cases.…”
Section: Discussionmentioning
confidence: 99%
“…The categorical variables comprise sex, patient class, service, primary physician, primary CPT, primary anesthesia type, location, and laterality. We reported that all the CPTs could be converted to relative value units (RVU) in a case length prediction model 14 . The RVU consists of 3 categories: physician work, practice expense, and professional liability.…”
Section: Methodsmentioning
confidence: 99%